PENERAPAN MODEL PEMBELAJARAN DIFERENSIASI PADA KURIKULUM MERDEKA - Shinta Hanani H; Irzak Yuliardy Nugroho; Saiful Islam (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the implementation of the differentiated learning model within the framework of the Merdeka Curriculum at MTs Mambaul Ulum Kaliacar Gading Probolinggo. The study employed a qualitative approach using a case study design. Research participants consisted of the madrasa principal, teachers, and students, who were selected through purposive sampling. Data were collected through observations, semi-structured interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation, while data analysis followed the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The findings indicate that differentiated learning has been implemented as an integral part of the Merdeka Curriculum through diagnostic assessment, content differentiation, process differentiation, and product differentiation. Teachers conducted an initial mapping of students’ learning needs prior to instruction, utilized a variety of learning resources, grouped students according to their readiness levels, and provided diverse task options based on students’ abilities and characteristics. The implementation of differentiated learning had a positive impact on students’ participation, motivation, self-confidence, and engagement in the learning process. Furthermore, it contributed to the creation of a more inclusive, participatory, and student-centered learning environment. However, several challenges were identified, including limited instructional time, relatively large class sizes, and inadequate learning facilities and media.